The Use of Gastrocnemius Muscle Flap in Reconstruction of Pretibial Defects - Karn, Binod (Journal of Nepalgunj Medical College, 2015)
Background: In Western part of Nepal the post traumatic lower leg and bone injuries with infected, open wound is common occurrence. Aim: It was to find out whether Gastrocnemius muscle flap is a viable option for pretibial defects. However variations in vascular anatomy of pedicle, use of reverse flow soleus muscle flap based on posterior tibial artery, leads to high failure rate and sacrificing major leg vessels. Method: Use of soleus muscle flap supported by perforating arteries, branches of posterior tibial vessels is option to cover small defects. The flap with careful newer modification to preserve vascularity, is used in 32 cases of pretibial defects. Observation: All 32 flaps survived with two cases in post operative phase, needing a flap elevation debridement of underlying bone and other skin grafting. Result: None of the case showed any vascular insufficiency, graft muscle loss or any functional loss. Use of muscle flap a viable option in pretibial defects. Journal of Nepalgunj Medical College Vol.12(1) 2014: 2-5